2022
DOI: 10.1177/09540083221111330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of layering angles on shape memory properties of graphene oxide/carbon fiber hybrid reinforced composites prepared by vacuum infiltration hot pressing system

Abstract: Seven groups of different layering angles of Graphene oxide/Carbon fiber (GO-CF) hybrid reinforced shape memory composites are prepared by vacuum infiltration hot pressing system. The layering angles are respectively [0°]4, [±15°]s, [±30°]s, [±45°]s, [±60°]s, [±75°]s, and [90°]4. The shape fixation ratio, shape recovery ratio, and shape recovery driving force of GO-CF hybrid reinforced shape memory composites are investigated. The composite with the layering angle of [0°]4 has the minimum shape fixation ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…21 From Figure 7 it can be seen that when the specimen is C6, it produces the largest value of maximum shape recovery force, which is 7.98 N. This is because the shape recovery force of the specimen is mainly composed of the fiber shape recovery force, matrix rebound force, and the internal stress stored in the specimen. 22 When the specimens are all CF, their elasticity modulus is the highest at 133.78 GPa, their bending force in the specimen is the highest during shape fixation, and their stored energy is the highest during cooling. During the heating process, the stored high energy starts to be released and CF with high elasticity modulus starts to rebound, so its maximum shape recovery force value is the largest.…”
Section: C6 G1c5 G2c4 G3c3 G4c2 G5c1 G6mentioning
confidence: 99%
“…21 From Figure 7 it can be seen that when the specimen is C6, it produces the largest value of maximum shape recovery force, which is 7.98 N. This is because the shape recovery force of the specimen is mainly composed of the fiber shape recovery force, matrix rebound force, and the internal stress stored in the specimen. 22 When the specimens are all CF, their elasticity modulus is the highest at 133.78 GPa, their bending force in the specimen is the highest during shape fixation, and their stored energy is the highest during cooling. During the heating process, the stored high energy starts to be released and CF with high elasticity modulus starts to rebound, so its maximum shape recovery force value is the largest.…”
Section: C6 G1c5 G2c4 G3c3 G4c2 G5c1 G6mentioning
confidence: 99%
“…Similarly, the study by Fejős et al [9] reported that the shape fixity and recovery rate were negatively impacted, but the recovery stress was enhanced because of the woven glass fiber reinforcement (37 vol.%). In another study, Xu et al [10] found that the stacking orientation of unidirectional carbon fiber has an effect on the shape-memory performance of the composite. Therefore, the fiber and matrix content should be balanced when considering the mechanical and shape-memory properties.…”
Section: Introductionmentioning
confidence: 97%